Evaluation of Parking Space needs for Marzoeki Mahdi Hospital - Firmansyah, Daarul; Rulhendri, Rulhendri; Alimuddin, Alimuddin (ASTONJADRO, 2026)
Dr. H. Marzoeki Mahdi Mental Hospital (RSJMM) Bogor is a type A mental hospital that is a referral for mental health and drug services located at Jalan dr. Sumeru No. 114, Bogor City. RSJMM has a land area of ​​56 hectares and a building area of ​​79,238 m2. RSJMM has a total of 590 beds and is supported by 944 employees as of May 2020 consisting of 64 medical personnel, 415 nursing staff, 66 other health workers and 310 non-medical personnel. RSJMM as a referral hospital has a wide coverage area covering the Bogor area and the western part of West Java Province. Its implementation as a Public Service Agency (BLU) hospital has an important role as one of the spearheads in public health development, has the task and responsibility to improve services to the community in order to advance public welfare and educate the nation's life with flexibility in financial management based on economic principles, productivity, and the implementation of healthy business practices. To realize these goals, the hospital refers to the principles of accountability, transparency, effectiveness, and efficiency. Of course, visits to the hospital will also increase, therefore it is necessary to have supporting facilities such as adequate parking areas so that visitors feel safe and comfortable when parking their vehicles. In this study using the SRP characteristic method (Volume, Accumulation, Duration, Over Turn Over, Index), in this study is the Evaluation of Parking space needs. Data collection was carried out using a survey method with a time of 10 hours and running for seven days with the aspects taken being the data on vehicle entry and exit times to determine parking characteristics. The results of this study indicate that the need for parking space cannot accommodate motorcycles, an area of ​​168m2 has a parking capacity of 74 SRP. In this analysis study, the results of the largest accumulated static capacity were 147 vehicles with an average parking duration of 09:48 hours on the peak day, namely Wednesday, February 11, 2025. During the seven days of the survey, it was found that the maximum parking volume was 169 vehicles with a maximum vehicle parking accumulation of 100 vehicles which occurred on Monday, February 17, 2025. The highest motorcycle parking turnover at Marzoeki Mahdi Hospital reached 234.75%, this shows that motorcycle parking performance is very high. The capacity of motorcycle parking space at Karya Bhakti Pratiwi Hospital cannot meet existing parking needs. This is indicated by looking at the parking index exceeding capacity.